“But Who Eats the Mosquitos?”: Deaf Learners’ Language Use and Translanguaging During STEAM Discussions - Jessica Scott; Patrick Enderle; Scott Cohen; Jasmine Smith; Reagan Hutchison (Education Sciences)
Science, technology, engineering, arts, and mathematics (STEAM) education represents an array of fields that have significant promise for the future careers of students. However, in deaf education, little research has been conducted to understand how best to provide access to STEAM learning opportunities for deaf students. This manuscript explores STEAM learning and Deaf Education through the lens of translanguaging. Translanguaging is the use of multiple linguistic resources by multilingual individuals. The authors recorded deaf teens attending a STEAM camp as they engaged in a collaborative problem-solving activity to explore the language resources they used to make sense of and communicate their understanding of the problem during various stages of the activity (gathering information, generating ideas, and evaluating ideas). We viewed their interactions through a translanguaging lens. We found that the campers used an array of both language-based (ASL, spoken English, gesture, and fingerspelling) and tool-based (writing on a whiteboard, engaging with informational papers, using computers or phones) translanguaging activities to gather information and communicate with one another. While selection of language resources did not differ by activity stage, they did differ by group, suggesting that campers were sensitive to the communication needs of their group mates.